From idea to implementation in protection of electronic editions - Mitrović, Časlav Borisav (Journal of Applied Engineering Science, 2011)
This work represents a study of electronic editions protection on optical discs (CD/DVD) based on basic principles of logic and code protection. The design of this solution is rather simple, but it is mainly similar to complex methods used nowadays in protection of great number of commercial electronic editions. The implementation and usage are adopted to users (students/professors) who are interested in electronic editions that are published on Criminal-Police Academy in Belgrade. Key words: CD, DVD, electronic editions, data protection.
Keywords: Data; DVD; CD; Logics; implementation; Electrons; Editing; protective